A CASE STUDY OF EXERGY ANALYSIS OF WASTE HEAT RECOVERY IN REFRIGERATION SYSTEM - Tršelič, Ivana; Avsec, Jurij (Journal of Energy Technology, 2024)
From an energy perspective, refrigeration systems employ a wasteful process; nevertheless, the food industry depends on refrigeration systems. To improve the efficiency of this process, a refrigeration system can be combined with a heating system, by using the waste heat from the condenser of the refrigeration system in the heating system. A case study of the application of a waste heat recovery system is considered in this paper. The conserved energy for three years is calculated, based on the literature, i.e. practical engineering articles. The numbers given are compared with the case study. The economic analysis reveals that the investment in an advanced refrigeration system is returned over a very short time. Two system models are discussed: a refrigeration system with no alternation and a refrigeration system that applies the recovery of waste energy. Exergy analysis has been developed for both models. The analysis shows an increase in the exergy efficiency of the advanced refrigeration system by 2%.